2021
DOI: 10.1007/s10967-021-08142-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating radiation risks and resource opportunities associated with phosphogypsum in the Philippines

Abstract: Phosphogypsum (PG) accumulates during wet-phosphoric acid production for fertilizers. In the Philippines, PG is partly (40%) utilized to produce gypsum walls and cement. This work assesses the radiological risks and resource opportunities associated with PG stacks in the Philippines. The conducted in situ radiometric survey measured the activity concentrations of 40K, 238U, and 232Th at 270 locations. Besides, another 120 surface samples were collected. Pure PG exceeds the recommended radiation limits, but sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The use of phosphogypsum is associated with challenges that have gained increasing importance [129], as shown in Figure 6. Furthermore, it should be noted that phosphogypsum may be contaminated with radionuclides [130]. According to EPA data, phosphogypsum contains significant quantities of uranium and its decay products, such as radium-226, attributed to its presence in phosphate ores.…”
Section: Possibility Of Using Phosphogypsum For Soil Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of phosphogypsum is associated with challenges that have gained increasing importance [129], as shown in Figure 6. Furthermore, it should be noted that phosphogypsum may be contaminated with radionuclides [130]. According to EPA data, phosphogypsum contains significant quantities of uranium and its decay products, such as radium-226, attributed to its presence in phosphate ores.…”
Section: Possibility Of Using Phosphogypsum For Soil Bioremediationmentioning
confidence: 99%
“…In terms of the content of radionuclide isotopes, the data vary significantly depending on the region of phosphogypsum deposition. A review of previous studies [130,141,142] showed that radioactivity varies according to the type of phosphate ore and is mainly caused by the decay series U-238 and Th-232. Since U-235 is not as common in nature as U-238, the radiation of this decay series is not considered a threat [143].…”
Section: Possibility Of Using Phosphogypsum For Soil Bioremediationmentioning
confidence: 99%
“…In sedimentary PR, for instance, U concentrations are in the range of 80-200 mg kg −1 [11]. Sedimentary PR accounts for approximately 80% of the PR mined globally, while in igneous PR, the U concentrations are typically much lower (around 30 mg kg −1 ) [11][12][13][14]. The application of P fertilizers can disseminate considerable amounts of U on agricultural soils that may leach from the soil to ground and surface waters [11,15].…”
Section: Introduction 1background Informationmentioning
confidence: 99%
“…Direct leaching of REEs from the phosphate ore or phosphate rock may be an attractive proposition since all REEs could theoretically be recovered and if done well the remaining ore matrix could simply be processed using present-day WPA production infrastructure. Besides, radioactive trace elements may also be extracted in this step so that the resulting phosphogypsum shows activity levels below regulatory control so that what is considered a lowlevel radioactive waste material in most countries today could be used as an inexpensive raw material in construction tomorrow [21][22][23].…”
Section: Introductionmentioning
confidence: 99%